Microbiological quality of bulk tank raw milk from two dairy farms in Hajdú-Bihar County, Hungary - Kojo Woode, Benjamin; Petróczki, Flóra; Béri, Béla; Peles, Ferenc (Acta Agraria Debreceniensis, 2018)
Two main channels have been identified to be responsible for microbiological contamination of raw milk and milk products. Firstly, contamination has occurred due to udder infection from the cow or the blood which harbours most bacteria that come in contact with the raw milk. Secondly, via external factors (may include faeces, skin, contaminated water, environment etc.) which are associated with the operation of milking. There is direct contact with the milk and/or surfaces before, during or after the milking, posing public health risk and economic decline. The aim of this study was to examine the bacteriological quality of bulk tank raw milk samples collected from two different size dairy farms (Farm 1 and Farm 2) of different housing forms (cubicle loose and deep litter) in Hajdú-Bihar County, Hungary in July, 2017. Three samples were taken from each farm, and the total plate count, coliform count, Escherichia coli count, Staphylococcus aureus count, and yeast and mould count were determined in them. The results clearly showed low level of all measured bacteria group load in Farm 1 samples in comparison to Farm 2 with the exception of coagulase-negative Staphylococcus (CNS) which represented high level in general, indicating significant difference (P<0.05). The mean value of total plate count in Farm 2 samples was higher (1.0 × 105 CFU/mL) than Farm 1 samples (2.8 × 104 CFU/mL). There was a significant difference (P<0.05) in mean count of coliforms in raw milk samples between Farm 1 and Farm 2. Similarly, results of E. coli were significantly different (P<0.05) with mean count of 1.44 × 102 CFU/mL and 2.02 × 103 CFU/mL for Farm 1 and Farm 2 respectively. Results of Staphylococcus aureus also showed significant difference (P<0.05) with mean count of 9.7 × 101 CFU/mL for Farm 1 and 6.28 × 102 CFU/mL for Farm 2. The mean of mould count recorded was 1.07 × 102 CFU/mL and 4.93 × 102 CFU/mL for Farm 1 and Farm 2 respectively. The recorded mean of yeast count was 1.68 × 103 CFU/mL and 3.41 × 103 CFU/mL for Farm 1 and Farm 2 respectively; however, both farms showed no significant difference (P>0.05) in terms of mean of mould and yeast count. Although Farm 2 produced six times lower milk quantity than Farm 1, the measured microbial parameters were high. Both farms’ microbiological numbers were higher above the permitted limit values as stated by Regulation (EC) No 853/2004, Hungarian Ministry of Health (MoH) 4/1998 (XI. 11.). This could be an indication of non-conformance to effective GMP, ineffective pre–milking disinfection or udder preparation, poor handling and storage practice, time and temperature abuse and inadequate Food Safety Management System Implementation. Therefore, our recommendation is as follows; establish control measures for pre- and postharvest activities involved in the milking process which would be an effective approach to reduce contamination of the raw milk by pathogenic microorganisms from these farms, strict sanitation regime and hygiene protocol be employed and applied to cows, all equipment, contact surfaces and minimize handling of the milk prior, during and after milking. This will also serve as scientific information to the producers for continual improvement in their operations.